SISTEM PENGELOLAAN DANA KOTAK INFAK DAN SEDEKAH KELILING MASJID DI PASAR 45 MANADO - Andi M. Fadly Taher; Suprijati Sarib; Rosdalina Bukido (IAIN Manado, 2016)
This paper is a case study entitled “Fund Management System of mobile Infaq and alm boxesin Pasar 45Manado”. This research was conducted using observationsin the area of Pasar45 Manado.Data were collected through observations and interviewswith the carriers of infaq boxes, the dwellers in Pasar45Manado, and people in charge of the infaq boxes management, as well as documentation. The approach used is juridical and sociological. This research aims (1) to understand the fund management system of theinfaqand almboxesspread around Pasar45, and the management by which collectors collect all of theinfaqand almboxes. Once the collectors collected the donation, they gave them to the mosque’s management who would divide the fund into two parts:40 percent for the collectors and the restis allocated for the construction of mosques and others. This research also seeks (2) to describe how people view the fund management system ofinfaq and alms boxes collected around Pasar45Manado. This research shows that most people seem to disfavor these alms and infaq collection due to the unstructured fund management. We need to understand that the infaq and alms boxes run by collectors every Friday to ask for a donation is a noble deed when the funds is channeled and addressed to the appropriate places orpeople or those who are in need. This action would certainly benefit the Muslim community.The funds will help to reduce poverty in Manado as well as in other areas. Yet sometimes the fund would not be donated entirely to the mosque but it goes to two divisions as previously mentioned